PENGEMBANGAN ALAT PERMAINAN EDUKATIF “KARTU BACA NGAJI ASYIK” UNTUK ANAK USIA DINI - Septiani Selly Susanti (AZZAHRA, 2020)
This research is useful for parents, teachers, and lecturers in an effort to create a tool that is able to condition learning to be fun and enjoyable for children. Childhood is a time when they prefer to play and move. Making children comfortable in the early childhood learning process is the main key. This is because the world of children is a world of joy, warmth, and joy, so that all activities intended for children must always give birth to comfort. Here, educational play tools become one of the media that can make children's learning fun and enjoyable. When children learn with pleasure, their brains will easily receive knowledge and life experiences well and quickly. The learning process for children becomes easy. In the book "Development of Educative Reading Card Game Tools - Fun Koran for Early Childhood" helps parents and teachers deliver hijaiyah reading material by playing letter cards. With the “Fun Reading-Koran Cards” it is hoped that it will no longer be a boring activity when children learn to read and recite the Koran. But it is a fun moment, because it is conveyed by playing. This book is certainly not free from mistakes or mistakes. Therefore, the authors hope that readers and observers are pleased to convey criticism and suggestions for the sake of being together.